An intergenerational audit for the UK: 2023 - Molly Broome; Adam Corlett; Sophie Hale; Charlie McCurdy; Cara Pacitti (Luxembourg Income Study (LIS), 2023)
Five years ago, our Intergenerational Commission set out the numerous threats to the UK's promise of intergenerational progress. More recently, the spotlight has once again fallen on this issue, but this time in the US, where the latest data has started to suggest that living standards for the millennials are catching up with, and on some measures even surpassing, the generations that came before them. This fifth Intergenerational Audit for the UK - part of the ESRC-funded Connecting Generations research programme - provides a comprehensive assessment of how living standards have changed for younger generations, in an attempt to shed some light on whether millennials in the UK have experienced a comparable improvement in their economic fortunes as their US counterparts. We show that, unlike in the US, welcome improvements to millennials' living standards in recent years in the UK have not gone far enough to close the long-standing generational gaps.
Keywords: 330